2018
DOI: 10.1186/s12885-018-4773-z
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis as a prognostic variable for the clinical outcome in patients with renal cell carcinoma: a systematic review and meta-analysis

Abstract: BackgroundTumor necrosis (TN) correlates with adverse outcomes in numerous solid tumors. However, its prognostic value in renal cell carcinoma (RCC) remains unclear. In this study, we performed a meta-analysis to evaluate associations between TN and cancer-specific survival (CSS), overall survival (OS), recurrence-free survival (RFS) and progression-free-survival (PFS) in RCC.MethodsElectronic searches in PubMed, EMBASE and Web of Science were conducted according to the PRISMA statement. Hazard ratios (HRs) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(44 citation statements)
references
References 52 publications
5
39
0
Order By: Relevance
“…2c). Necrosis, a feature associated with tumour aggressiveness 13 , harsh hypoxic environmental conditions 13 and poor prognosis 14 , was additionally found (as expected) to be signi cantly higher in the tumour centre (p=0.006, Fig. 2d).…”
Section: Macroscopic Image Work Ow and Data Integration Pipelinesupporting
confidence: 74%
See 1 more Smart Citation
“…2c). Necrosis, a feature associated with tumour aggressiveness 13 , harsh hypoxic environmental conditions 13 and poor prognosis 14 , was additionally found (as expected) to be signi cantly higher in the tumour centre (p=0.006, Fig. 2d).…”
Section: Macroscopic Image Work Ow and Data Integration Pipelinesupporting
confidence: 74%
“…Given these additional competencies, it is thus unsurprising that subclones from the tumour centre are better adapted to seed secondary metastatic sites. Necrotic primary tumour subclones have been shown to have greater propensity to seed metastases in pre-clinical models 17 , and clinically a recent systematic meta-analysis across 34 studies demonstrated tumour necrosis to be associated with reduced cancerspeci c survival in RCC 14 . Biologically, tumour necrosis is classically associated with chronic hypoxia caused by rapid tumour growth and inadequate blood supply 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis has been associated with poor prognosis in a variety of cancer types. [7][8][9] Dying/necrotic tumor cells release intracellular contents/ factors in the TME and thus alter the extracellular milieu. One of the key factors that have recently been identified is an accumulation of increased amount of extracellular potassium ([K + ] e ) in the fluid around tumors (8-15-fold higher than that present in normal serum).…”
Section: Introductionmentioning
confidence: 99%
“…We and others reported candidate biomarkers, such as long non-coding RNAs, 9 gene expression signatures, [10][11][12][13][14][15] epigenetics 16 for ccRCC progression and/or survival. [17][18][19] However, there is currently no clinically accepted molecular biomarker for ccRCC progression.…”
Section: Introductionmentioning
confidence: 99%